From Bestial to Human: Neo-Mythological Reinterpretations of the Image of Delilah in Russian Literature at the Turn of the 20th-21st Centuries - Šroma, Nataļja (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The article examines one of the eternal images of the world culture in a diachronic aspect, namely the interpretation and reinterpretation of the image of Delilah in Russian literature, primarily in poetry, from the 19th century to the present day. The novelty of the article involves the introduction into the scientific context of a number of neo-mythological texts and the provided scholarly commentary, as well as the study of the poetics of the myth and neo-myth with an emphasis on the ethical aspect in the context of ideas of Dmitry Ovsyaniko-Kulikovsky.The relevance of the goal is connected with the opportunity to solve several interrelated scientific problems, since the functioning of mythological images and biblical stories, more precisely, the vector of conceptualization of their meanings, makes it possible not only to understand the specifics of the culture of perception, but also to evaluate the moral condition of society.In the course of the study, the following trends in the reception of the plot were identified: a consistent shift in the interest of Russian authors from the character of Samson to Delilah, a change in the system of characters and methods of narration, a change in the modality of the image of Delilah, her transformation into a predominantly idyllic character. Particular attention in the article is paid to the political conceptualization of the image of Delilah, which is associated with the inclusion of the plot into the so-called barber text of Russian literature and culture.The author of the article comes to the conclusion that the image of Delilah becomes conceptually dual in modern neo-mythological reinterpretations. The humanization of the image of Delilah, her evolution from bestial to human can be traced in love poetry. The refocusing of the authors’ attention from Samson to Delilah in social poetry leads to an increase in her role in the eternal plot, turning her into a politically ideological killer. The conducted research may also be interesting in the aspect of gender studies, since the analyzed material gives grounds to consider the image of Delilah in modern Russian literature as one of the representations of the femme fatale.